Generations - Tan, Jean Zhiye (2015)
Generations is an art installation, which brings back the environmental and historical memories of previous generations’ in Singapore, namely the 1960s-1980s. The project looks into the local history and brings out information of the previous generations’ daily life. The whole exhibition also provided an experience of re-living the kampong days as the audience walked past the various objects, accompanied by a short text that described the daily environmental and historical happenings back then.